Saccostrea Dollfus & Dautzenberg 1920 - Wells, Fred E.; Lukehurst, Sherralee S.; Fullwood, Laura A. F.; Harvey, Euan S. (Zenodo, 2024)
Saccostrea lineage A (Figures 2a, c, 3; Table 1) Brief description of shell: Often densely packed so shells grow to fit available space. Medium size, oval, length 5 cm or less, hinge to tip of shell. Margins crenulated, margins may have short lobes that can be worn off. Outer surface off white. Inner white, adductor scar on left valve purple. Oysters grown individually for aquaculture up to 6 cm, elongate, left valve deeper. Records in the present survey: Ashburton Port area: East end Thevenard Island; Hooley Creek; Salt Creek; Beadon Creek jetty; Four Mile Creek. Dampier Port area: Withnell Bay, Burrup Peninsula; Southern entrance to King Bay; Eastern King Bay; Dampier boat landing; Watering Cove, Burrup Peninsula; Karratha Bay, West Lewis Island; North side of East Intercourse Island. Port Samson port area: Point Samson. Port Hedland Port area: Public boat ramp, Port Hedland reef, Pretty Pool. Previous records in the Pilbara verified by DNA sequences: Lam and Morton (2006): Exmouth; Barrow Island; Watering Cove; Withnell Bay. Snow et al. (2023): Flying Foam Passage, north of Burrup Peninsula. Notes: Saccostrea lineage A occurred on a wide variety of habitats including lying loose on intertidal sandflats, and attached to isolated rocks, intertidal rock platforms, mangroves and artificial structures on both protected and open shores, sometimes at high densities. It frequently co-occurred with S. scyphophilla, but was more common on protected shores than S. scyphophilla . Saccostrea cuccullata (Born, 1778) was regarded as a widespread Indo- Pacific species with a variable shell morphology (Harry 1985), but recent DNA sequencing has divided the “species” into a number of separate genetic lineages (e.g. Lam and Morton 2006; Sekino and Yamashita 2016; McDougall 2020; Snow et al. 2023). The taxonomic status of the various lineages is uncertain. Oysters previously identified as S. cuccullata may in fact be a species complex, with each lineage representing a separate species (McDougall 2020). Lam and Morton (2006) ...